Representing the New World - Hart, J. author. aut Link
352 p.
Keywords: Representing the New World argues for the importance of Spain in the New World as an example of France and England in their efforts to establish colonies and suggests that this example was ambivalent and contradictory as well as surprisingly persistent in the representations of Spain in French and English texts concerning the Americas.